Effects of copper nanoparticles on the morphological and physiological changes in chicken - Xuan, Nguyen Thi; Trang, Phi Thi Thu; Hien, Le Thi Thu (Academia Journal of Biology, 2019)
Copper nanoparticles (nCu) have a wide range of applications in many different fields of life. In poultry farming, nCu is well-known as a feed additive to stimulate the development, a good antimicrobial agent and a suppressor of diarrhea. The aim of this study is to perform the analysis of biosafety of nCu. In this study, chickens were treated with drinking water containing 2 mg/L or 1000 mg/L nCu. After 5 weeks of treatment, the survival rate, dry body weight, Cu content in serum and liver tissues of chickens were examined. Liver and kidney functions were also determined by measuring serum levels of ALT, AST, and creatinine. As a result, chickens treated with drinking containing 2 mg/L nCu had no changes in liver and kidney functions as well as their body weights. However, treatment of chickens with 1000 mg/L nCu caused accumulationof Cu in the serum and liver and increase of the serum levels of ALT and AST compared with control group. Apparently they sick and did not develop properly. In conclusion, nCu concentration at 2 mg/L may be recommended for the agricultural, feed and medicine formulations to meet biological safety.ALT, AST, creatinine, nCu, chicken.